1989
DOI: 10.1177/153857448902300402
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Surgery in Chinese Septuagenarians

Abstract: Arteriosclerosis has been well known to be intimately connected with the human aging process, and thus the prevalence of coronary artery disease increases with the advance of age.On the other hand, senility seems to cause extra surgical risk when a patient undergoes a major operation such as coronary artery revascularization. In the past, physicians, and perhaps patients too, took a conservative attitude toward coronary artery bypass surgery for aged patients. But in the author's experience with 38 patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Interestingly, Khan et al [16] have suggested that models for predicting outcome after CABG should be tested for potential interactions between age and risk factors. In our previous series, we also found that older patients had prolonged ICU stay and hospitalization following CABG surgery [17]. Moreover, Olsen et al [18] recommended that cardiovascular risk prediction by NT-proBNP was affected by age.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, Khan et al [16] have suggested that models for predicting outcome after CABG should be tested for potential interactions between age and risk factors. In our previous series, we also found that older patients had prolonged ICU stay and hospitalization following CABG surgery [17]. Moreover, Olsen et al [18] recommended that cardiovascular risk prediction by NT-proBNP was affected by age.…”
Section: Discussionmentioning
confidence: 77%